PEMBENTUKAN DAN PERKEMBANGAN TASAWWUF FALSAFI - M Miswar (STIT Al-Ittihadiyah Labuhanbatu Utara, 2019)
Falsafi Sufism is a concept of Sufism teaching that knows God (ma'rifat) with the ratio approach (philosophy) to go to a higher level, not only knowing God (ma'rifatullah) but higher than that is wihdatul wujud (form unity of being). It could also be said that philosophical Sufism is Sufism which is rich in philosophical thoughts. Philosophy Sufism is an interesting discussion to discuss. In this paper we will discuss the formation and development of philosophical-philosophical thinking (philosophical Sufism) which consists of: understanding Sufism of Falsafi; characteristics of philosophical Sufism; philosophical background and sources of Sufism; the historical development of philosophical Sufism; and philosophical Sufism figures and teachings